2023
DOI: 10.1177/23727322231197739
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Electroencephalography With Black Individuals: Barriers, Recommendations, and Impact on Generalizability

Lisa Brown,
David Rollock,
Dan Foti

Abstract: Electroencephalography (EEG) is a critical tool for neuroscience research on brain functioning, as well as clinical applications in neurological and psychiatric illnesses. Anti-Black racism is a substantial societal problem that affects the validity of EEG assessments, thereby undermining efforts in research and in medical practice. There are several barriers present in the process of recording EEG with Black individuals. This includes the physical qualities of Black hair; as well as the cultural and historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…These same systems of racial oppression and structural racism have resulted in a higher distribution of Black families living in lower-income environments [230,231], indicating that rsEEG studies examining socioeconomic differences may not be representative of individuals from diverse racial groups. To promote diversity in the participants recruited for EEG studies, researchers should consider engaging Black researchers in both the development and execution of EEG research, as this has been shown to result in a more positive experience for the participant while also collecting useful data [232][233][234][235]. Providing hair care products that are conducive to Black hair may also promote inclusivity and make the cleanup process less burdensome for participants [233,236].…”
Section: Considerations For Texture and Style Of Hair In Neuroimaging...mentioning
confidence: 99%
See 1 more Smart Citation
“…These same systems of racial oppression and structural racism have resulted in a higher distribution of Black families living in lower-income environments [230,231], indicating that rsEEG studies examining socioeconomic differences may not be representative of individuals from diverse racial groups. To promote diversity in the participants recruited for EEG studies, researchers should consider engaging Black researchers in both the development and execution of EEG research, as this has been shown to result in a more positive experience for the participant while also collecting useful data [232][233][234][235]. Providing hair care products that are conducive to Black hair may also promote inclusivity and make the cleanup process less burdensome for participants [233,236].…”
Section: Considerations For Texture and Style Of Hair In Neuroimaging...mentioning
confidence: 99%
“…To promote diversity in the participants recruited for EEG studies, researchers should consider engaging Black researchers in both the development and execution of EEG research, as this has been shown to result in a more positive experience for the participant while also collecting useful data [232][233][234][235]. Providing hair care products that are conducive to Black hair may also promote inclusivity and make the cleanup process less burdensome for participants [233,236]. Although new organizations such as Black in Neuro (blackinneuro.com) and SPARK Society (sparksociety.org) are conducting foundational work to raise awareness about systemic racism in neuroscience, researchers can also consider ways by which their EEG methods can be revised to promote diversity, equity, and inclusion.…”
Section: Considerations For Texture and Style Of Hair In Neuroimaging...mentioning
confidence: 99%